Bindarit, an Inhibitor of Monocyte Chemotactic Protein Synthesis, Protects against Bone Loss Induced by Chikungunya Virus Infection - Weiqiang Chen; Suan‐Sin Foo; Adam Taylor; Aleksei Lulla; Andres Merits; Linda Hueston; Mark R. Forwood; Nicole C. Walsh; Natalie A. Sims; Lara J. Herrero; Suresh Mahalingam (2014)
ABSTRACT The recent global resurgence of arthritogenic alphaviruses, in particular chikungunya virus (CHIKV), highlights an urgent need for the development of therapeutic intervention strategies. While there has been significant progress in defining the pathophysiology of alphaviral disease, relatively little is known about the mechanisms involved in CHIKV-induced arthritis or potential therapeutic options to treat the severe arthritic symptoms associated with infection. Here, we used microcomputed tomographic (μCT) and histomorphometric analyses to provide previously undescribed evidence of reduced bone volume in the proximal tibial epiphysis of CHIKV-infected mice compared to the results for mock controls. This was associated with a significant increase in the receptor activator of nuclear factor-κB ligand/osteoprotegerin (RANKL/OPG) ratio in infected murine joints and in the serum of CHIKV patients. The expression levels of the monocyte chemoattractant proteins (MCPs), including MCP-1/CCL2, MCP-2/CCL8, and MCP-3/CCL7, were also highly elevated in joints of CHIKV-infected mice, accompanied by increased cellularity within the bone marrow in tibial epiphysis and ankle joints. Both this effect and CHIKV-induced bone loss were significantly reduced by treatment with the MCP inhibitor bindarit. Collectively, these findings demonstrate a unique role for MCPs in promoting CHIKV-induced osteoclastogenesis and bone loss during disease and suggest that inhibition of MCPs with bindarit may be an effective therapy for patients affected with alphavirus-induced bone loss. IMPORTANCE Arthritogenic alphaviruses, including chikungunya virus (CHIKV) and Ross River virus (RRV), cause worldwide outbreaks of polyarthritis, which can persist in patients for months following infection. Previous studies have shown that host proinflammatory soluble factors are associated with CHIKV disease severity. Furthermore, it is established that chemokine (C-C motif) ligand 2 (CCL2/MCP-1) is important in cellular recruitment and inducing bone-resorbing osteoclast (OC) formation. Here, we show that CHIKV replicates in bone and triggers bone loss by increasing the RANKL/OPG ratio. CHIKV infection results in MCP-induced cellular infiltration in the inflamed joints, and bone loss can be ameliorated by treatment with an MCP-inhibiting drug, bindarit. Taken together, our data reveal a previously undescribed role for MCPs in CHIKV-induced bone loss: one of recruiting monocytes/OC precursors to joint sites and thereby favoring a pro-osteoclastic microenvironment. This suggests that bindarit may be an effective treatment for alphavirus-induced bone loss and arthritis in humans.